Bioactivities of helichrysum cymosum cultivated in aquaponic, hydroponic and field systems - Zantanta Nomnqophiso; Learnmore Kambizi; Ninon G.E. Etsassala; Felix Nchu (AOSIS, 2024)
Background: Aquaponics and hydroponics are potential alternative techniques for sustainable cultivating of medicinal plants. Setting: The experiments were carried out on the Bellville campus of the Cape Peninsula University of Technology, Cape Town, South Africa. Aim: The aim of this study was to evaluate crop yield, secondary metabolite contents, and the antifungal activities of extracts from Helichrysum cymosum (H. cymosum) grown in aquaponic and hydroponic systems compared with field-collected plants. Methods: Helichrysum cymosum seedlings were cultivated in hydroponic and aquaponic systems for 6 weeks under greenhouse conditions. The data on plant growth parameters, phytochemical analyses of the leaves, anti-Fusarium oxysporum (F. oxysporum) activity of ethanolic extracts, and antioxidant capacities were recorded. Results: The results showed that the heights of plants grown in aquaponics and hydroponics did not differ substantially (p 0.05). The total polyphenol contents varied significantly (p 0.01) among the three cultivation techniques, with the field-collected plants yielding the highest contents (452.10 mg GAE/g ± 53.37 mg GAE/g). The flavonol contents differed significantly among the three cultivation techniques (p 0.05), with the highest flavonol contents in the field-collected plants (250.62 mg QE/g ± 58.12 mg QE/g). The plants grown in aquaponics had the highest number of compounds (104). The microdilution bioassay showed that the ethanolic extracts of field-harvested H. cymosum had higher fungistatic activity against F. oxysporum. The highest antioxidant capacity was recorded in 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay for plants cultivated in hydroponics (p 0.05), while field-collected plants showed a significantly higher value of 2719.42 µmol ± 278.72 µmol AAE/g (p 0.05) in the ferric ion reducing antioxidant parameter (FRAP) assay. Conclusion: The field-collected plants performed better in phytochemical contents. However, cultivation of H. cymosum using a hydroponic system may be feasible based on the antioxidant results. Contributions: The study contributes to developing an alternative strategy for cultivating plants and promoting sustainable farming.